2020
DOI: 10.1371/journal.pone.0231216
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of the Brazilian Workers’ Food Program on the nutritional status of manufacturing workers: A population-based prospective cohort study

Abstract: Background The Brazilian Workers Food Program (WFP) is a public policy program of nutritional assistance to workers, with the main objective of improving nutritional conditions, which was implemented 40 years ago and serves over 21.4 million workers. Objectives To compare the long-term change in anthropometric indicators of the nutritional status and dietary intake between workers of manufacturing industries adherent to and non-adherent to the WFP. Methods A prospective cohort study, based on a combined strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
(16 reference statements)
0
5
0
7
Order By: Relevance
“…This finding confirms the hypothesis of an increase in BMI and WC indices and a higher prevalence of overweight and obesity in workers, which could be due to their adherence to the WFP. In addition, this requires the better monitoring of the program so as to regulate the nutritional quality of the meals provided, thereby achieving better results in terms of the workers' nutritional status [39]. This finding may be explained by increased energy intakes of participants in the WFP group compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…This finding confirms the hypothesis of an increase in BMI and WC indices and a higher prevalence of overweight and obesity in workers, which could be due to their adherence to the WFP. In addition, this requires the better monitoring of the program so as to regulate the nutritional quality of the meals provided, thereby achieving better results in terms of the workers' nutritional status [39]. This finding may be explained by increased energy intakes of participants in the WFP group compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, with the progressive improvement in wealth and social conditions in Brazil, the nutritional parameters defined by the WFP suffered several reformulations in order to maintain its commitment to the food and nutritional security of workers. However, several studies that have assessed the relationship between the WFP and the nutritional status of workers have consistently shown a high prevalence of overweight and obesity among workers from companies that adhere to the program, [6][7][8][9] which goes against the main objective of the program. The results of the present study corroborate those found in the literature since, after adjustment for co-variates, it was observed that the prevalence of MetS was higher among manufacturing workers from companies adherent to the WFP.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its relevance and wide reach, the program was the focus of several studies aiming to evaluate the offered food and its impact on the nutritional and health status of workers. [6][7][8][9] Some results, however, have pointed to an inadequate nutritional offer, with excesses in energy, protein and lipid supply, in addition to reduced presence of fruits and vegetables on the menus. Comparative studies between companies adherent and non-adherent to the WFP have found greater prevalence of overweight and obesity, in addition to higher values of waist circumference (WC) in workers of WFP-adherent industries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The programme encourages firms to provide adequate food to their employees, prioritising workers who receive up to the equivalent of 5 times the minimum wage, but there is a possibility to extend it to workers with income above this limit. Any company can join the programme, including individual micro-entrepreneurs, microenterprises, non-profit companies, as well public or semi-public administrations and entities (Torres KG, 2020 [30]). Up to 30% of employers registered in the programme choose canteens, whilst 70% provide food and meal vouchers.…”
Section: Brazilmentioning
confidence: 99%